Design and Research of Climbing Mechanism based on Gear Rack Transmission - Hu Jie; Wang Zhanli; Chen Yanwei; Huang Sicong (Jixie chuandong)
A climbing mechanism based on the gear rack transmission is proposed. From the actual motion of the system and the device flip climbing movement conditions,the mathematical model is built,on the premise of guarantee stability margin,the optimal climbing posture is got. The key parts are analyzed by using the finite element analysis method. At the same time,from the standpoint of improving the degree of automation of device,the flip climbing progress control flow chart is established,the foundation for control system design is provided.